Heterostructured α‐Fe2O3@ZnO@ZIF‐8 Core–Shell Nanowires for a Highly Selective MEMS‐Based ppb‐Level H2S Gas Sensor System. Issue 50 (30th October 2022) - Zhu, Li‐Yuan; Miao, Xiao‐Yong; Ou, Lang‐Xi; Mao, Li‐Wen; Yuan, Kaiping; Sun, Shuhui; Devi, Anjana; Lu, Hong‐Liang
Abstract: Highly selective and sensitive H2 S sensors are in high demand in various fields closely related to human life. However, metal oxide semiconductors (MOSs) suffer from poor selectivity and single MOS@metal organic framework (MOF) core–shell nanocomposites are greatly limited due to the intrinsic low sensitivity of MOF shells. To simultaneously improve both selectivity and sensitivity, heterostructured α‐Fe2 O3 @ZnO@ZIF‐8 core–shell nanowires (NWs) are meticulously synthesized with the assistance of atomic layer deposition. The ZIF‐8 shell with regular pores and special surface functional groups is attractive for excellent selectivity and the heterostructured α‐Fe2 O3 @ZnO core with an additional electron depletion layer is promising with enhanced sensitivity compared to a single MOS core. As a result, the heterostructured α‐Fe2 O3 @ZnO@ZIF‐8 core–shell NWs achieve remarkable H2 S sensing performance with a high response ( R air / R gas = 32.2 to 10 ppm H2 S), superior selectivity, fast response/recovery speed (18.0/31.8 s), excellent long‐term stability (at least over 3 months), and relatively low limit of detection (down to 200 ppb) at low operating temperature of 200 °C, far beyond α‐Fe2 O3 @ZIF‐8 or α‐Fe2 O3 @ZnO core–shell NWs. Furthermore, a micro‐electromechanical system‐based H2 S gas sensor system with low power consumption is developed, holding great application potential in smart cities. Abstract : Heterostructured α‐Fe2 O3 @ZnO@ZIF‐8 core–shell nanowires are meticulously synthesized with the assistance of atomic layer deposition to simultaneously improve both selectivity and sensitivity as gas sensors. As a result, remarkable ppb‐level H2 S sensing performance is achieved. Furthermore, a micro‐electromechanical system‐based H2 S gas sensor system with low power consumption is developed, holding great application potential in smart cities.